2014
DOI: 10.1161/circimaging.113.001047
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Nonobstructive and Obstructive Coronary Artery Disease Detected by Coronary Computed Tomography Angiography to Identify Cardiovascular Events

Abstract: Several large, recent studies have demonstrated the impact of coronary CTA on prognosis, although the follow-up time has been relatively short.1,2 Only 1 study has evaluated the longer term follow-up of cardiovascular events among patients referred for coronary CTA.3 Because patients referred forBackground-The contribution of plaque extent to predict cardiovascular events among patients with nonobstructive and obstructive coronary artery disease (CAD) is not well defined. Our objective was to evaluate the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(234 citation statements)
references
References 37 publications
11
215
1
7
Order By: Relevance
“…88 89 The lower incidence of STEMI and the concomitant increase in less lipid laden and inflamed plaques in the statin era raise similar notes of caution regarding the interpretation of and goals of imaging studies. Others share this view, refer to "the myth of the vulnerable plaque", and propose that the management of patients at risk of MI mandates a greater focus on atherosclerotic disease burden than on features of individual plaques 52 , an inference that derives support from studies with coronary computed tomography angiography in patients with non-obstructive coronary artery disease 90 .…”
Section: Imaging Of the Atherosclerotic Plaque At Riskmentioning
confidence: 99%
“…88 89 The lower incidence of STEMI and the concomitant increase in less lipid laden and inflamed plaques in the statin era raise similar notes of caution regarding the interpretation of and goals of imaging studies. Others share this view, refer to "the myth of the vulnerable plaque", and propose that the management of patients at risk of MI mandates a greater focus on atherosclerotic disease burden than on features of individual plaques 52 , an inference that derives support from studies with coronary computed tomography angiography in patients with non-obstructive coronary artery disease 90 .…”
Section: Imaging Of the Atherosclerotic Plaque At Riskmentioning
confidence: 99%
“…The importance of total coronary plaque burden was highlighted recently by a study (31) whose results showed that diffuse nonobstructive coronary artery disease is associated with rates of cardiovascular death and myocardial infarction that are comparable with those of obstructive coronary artery disease. Therefore, the assessment of total coronary plaque at coronary CT angiography may be clinically relevant and enhance risk stratification.…”
Section: Cardiac Imagingmentioning
confidence: 99%
“…Studies with CCTA have also demonstrated the prognostic value of some of these detailed plaque features like positive remodeling, the presence of low attenuation plaques and the presence of a napkin ring sign. Since several coronary plaques are frequently found in the coronary tree even in low to intermediate CAD probability patients undergoing CCTA to rule out coronary stenosis (15,16), and since detailed plaque evaluation is time consuming, requires very good image quality and can be associated with low interobserver variability, another possible approach is to provide the total coronary atherosclerotic burden as a score, and some have been developed and validated as prognostic tools (17)(18)(19), providing imagers and researcher with additional tools and a change of focus from just the vulnerable plaque to the vulnerable coronary tree (20).…”
Section: Mini-reviewmentioning
confidence: 99%
“…In fact, lesions in this last subgroup can be considered "false negative" of CCTA and might explain the worse than expected prognosis of patients that don't have obstructive lesions but have high disease burden, as it has been recently demonstrated with the use of CCTA coronary atherosclerotic burden scores (17)(18)(19) that take in consideration all lesions independent of stenosis severity. As the knowledge of coronary disease pathophysiology advances, the traditional anatomic-based dichotomic concept of obstructive vs. nonobstructive is becoming more and more outdated and becoming replaced by a concept of high vs. low risk plaque features/burden, more in line with the recent evidence provided by both invasive and noninvasive atherosclerosis imaging.…”
Section: Atherosclerotic Plaque Characteristics and Functional Informmentioning
confidence: 99%